PERBANDINGAN MINYAK KACANG SACHA INCHI DAN MINYAK JAGUNG DALAM PEMBUATAN SELAI COKLAT SACHA INCHI COMPARISON OF SACHA INCHI PEANUT OIL AND CORN OIL IN MAKING SACHA INCHI CHOCOLATE SPREAD - Isima, Putri Fadjarwati; Salimi, Yuzda K; Isra, Muhammad (Jambura Journal of Food Technology, 2025)
Sacha inchi chocolate spread is an innovation of sacha inchi peanut butter jam product with sacha inchi oil and corn oil substitution. This study evaluated the effect of Sacha Inchi oil and corn oil substitution on the physicochemical and sensory characteristics of peanut chocolate spread. The purpose of this study was to determine the effect of oil composition on water content, protein content, viscosity, antioxidant activity, spreadability, and sensory attributes. This study used a Completely Randomized Design with three formulations: peanut butter with 6% corn oil, 6% Sacha Inchi oil, and a combination of 3% corn oil and 3% Sacha Inchi oil. Physicochemical parameters were analyzed using standard laboratory methods, while sensory evaluation was carried out by 30 untrained panelists using a seven-point hedonic scale. Statistical analysis was performed using one-way Analysis of Variance followed by Duncan's Test at a significance level of 5%. The results showed that the formulation with 6% Sacha Inchi oil had the highest viscosity (71.08Pa.s), and antioxidant activity (51.42µg/mL), while the formulation with 6% corn oil had the best spreadability (3.07). The combination formulation produced a balance between physicochemical and sensory characteristics and obtained high consumer preference scores for taste (5.30), texture (5.03), aroma (4.50), and color (4.83). The lowest water content was found in the formulation with Sacha Inchi oil, which contributed to better oxidative stability. The high antioxidant activity in the formulation with Sacha Inchi oil indicates its potential in extending the shelf life of the product.Keywords: Sacha inchi chocolate spread, Sacha Inchi oil, corn oil, physicochemical properties, sensory evaluation, antioxidant activity.